Membangun Harmoni Beragama Melalui Paradigma Inklusif - Maula, Finayatul (LoroNG: Media Pengkajian Sosial Budaya, 2015)
Issue of violence and conflict in religion recently is close from the complex triggers as well as the impact of globalization, misinterpretation of Illahi verses, depletion of religious tolerance, fanaticism class, political factor and other interests. As an effort of the resolution to this religion conflict, it is required concrete solutions that could thrive to an inclusive paradigm for religious life which is fraught of harmony and peace. Inclusive understanding is a point of view that does not claim the own religion to be the righteous one, but also deems others true. Being inclusive can be defined as believing that a truth is not a monopoly of a particular religion, but the truth can be found in other religions. Isu kekerasan dan konflik dalam beragama akhir-akhir ini tentu tak jauh dari faktor pemicu yang kompleks, seperti halnya dampak dari globalisasi, salah menginterpretasi ayat Illahi, menipisnya toleransi antar agama, fanatisme golongan, maupun faktor kepentingan politik dan yang lainnya. Sebagai upaya untuk meresolusi konflik keagaman ini dibutuhkan solusi nyata berupa paradigma inklusif yang bisa mengantarkan kepada kehidupan beragama yang harmoni dan penuh dengan perdamaian. Pemahaman yang inklusif yakni pemahaman yang tidak mengklaim diri sebagai satu-satunya yang benar, tapi juga memungkinkan orang lain juga benar. Menjadi inklusif berarti percaya bahwa kebenaran tidak menjadi monopoli agama tertentu, tetapi juga bisa ditemukan dalam agama-agama lain.